Selective monoformylation of naphthalene-fused propellanes for methylene-alternating copolymers - Kato, Kenichi; Hiroi, Tatsuki; Okada, Seina; Ohtani, Shunsuke; Ogoshi, Tomoki (Beilstein Journal of Organic Chemistry, 2025)
Development of three-dimensional (3D) building blocks is a key to change tight molecular assemblies of rigid π-conjugated planes into organic functional materials endowed with molecular-size cavities. To increase the diversity of available 3D building blocks, we herein report electrophilic formylation of naphthalene-fused [3.3.3]- and [4.3.3]propellanes as the first selective single-point functionalization by virtue of through-space electronic communications between the naphthalene units. The propellane skeletons have well-defined 3D structures and moderate flexibility at the same time. Therefore, the monoformyl products are good precursors for soft materials which show molecular-size cavities and require desymmetrized building blocks. As a proof of concept, methylene-alternating copolymers were prepared by reduction to corresponding alcohols followed by acid-mediated condensation. The linear copolymers show good solubility and carbon dioxide adsorption.
Keywords: alternating copolymer; building block; formylation; gas adsorption; propellane